KUALIFIKASI BADAN USAHA PADA PENGEMBANGAN UNIT USAHA PADA GRUP USAHA BUMN - Kristianto P H; Tivana Arbiani Candini (Universitas Katolik Indonesia Atma Jaya, 2019)
Specifically related to companies owned by the state, Law No. 19 of 2003 concerning State Owned Enterprises (BUMN Law), it is explained that SOEs are business entities whose entire or most of their capital is owned by the state through direct participation from the separated state assets.Furthermore, each state-owned company in its development can develop its business units into an independent business entity whose shareholders are state-controlled companies and whose capital comes from company assets controlled by the state and not from direct participation in state assets. separated. The difference in authorized capital between a company controlled by the state and a subsidiary of a company controlled by the state can lead to unclear legal status of the business entity or legal entity of a subsidiary controlled by the state because based on BUMN Law, a BUMN is only qualified as a BUMN if the capital is obtained from the investment directly from the country's wealth. Furthermore, the status of BUMN in Indonesian business activities has several priorities that have been determined by laws and regulations, so that the clarity of the status of a subsidiary of a state-controlled company needs to be further studied.